1999
DOI: 10.1002/(sici)1099-0992(199903/05)29:2/3<259::aid-ejsp927>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐structural characteristics of intergroup relations and identity management strategies: results from a field study in East Germany

Abstract: In a ®eld study in East Germany, predictions by Social Identity Theory concerning relations among socio-structural characteristics of intergroup relations (stability, legitimacy, permeability) and identity management strategies (e.g. social competition) were examined. In general, East Germans were expected to consider their status position as inferior compared to West Germans. Moreover, depending on whether they regard such a status di€erence as legitimate or illegitimate, as stable or unstable, and whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
2
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(129 citation statements)
references
References 16 publications
(30 reference statements)
9
116
2
2
Order By: Relevance
“…Another way of coping with negative collective emotions is to adopt identity negotiation strategies to achieve a positive social identity (Deaux & Ethier, 1998). According to social identity theory (Mummendey, Klink, Mielke, Wenzel, & Blanz, 1999;Tajfel & Turner, 1979), identity strategies can be personal (leaving the ingroup) or collective (e.g., using new dimensions for ingroup comparisons; changing group values; changing the comparison groups; and entering into competition with the outgroup) depending on the specific intergroup context.…”
Section: Collective Responsibility and Collective Emotionsmentioning
confidence: 99%
“…Another way of coping with negative collective emotions is to adopt identity negotiation strategies to achieve a positive social identity (Deaux & Ethier, 1998). According to social identity theory (Mummendey, Klink, Mielke, Wenzel, & Blanz, 1999;Tajfel & Turner, 1979), identity strategies can be personal (leaving the ingroup) or collective (e.g., using new dimensions for ingroup comparisons; changing group values; changing the comparison groups; and entering into competition with the outgroup) depending on the specific intergroup context.…”
Section: Collective Responsibility and Collective Emotionsmentioning
confidence: 99%
“…It has been repeatedly shown that when resources are limited intergroup competition is more likely to occur (Brewer, 1986;Esses, Jackson, & Armstrong, 1998;LeVine & Campbell, 1972;Sherif, 1966). For example, in a minimal group setting, Mummendey and Schreiber (1983) found that intergroup bias was drastically reduced when a less restrictive modality of comparison (e.g., in-group outcomes were independent of those of the out-group) was employed (see also Monacelli, Sari, & Carugati, 2000;Mugny, Sanchez-Mazas, Roux, & Pérez, 1991). On the basis of these findings, we argue that for social identity of intermediate status group members, limited resources condition should be more threatening (e.g., downward displacement is more likely to occur) than unlimited resources condition.…”
Section: Aim and Hypothesesmentioning
confidence: 99%
“…The individual's sense of positive self-identity serves as another affective determinant. A low sense of positive self-identity (such as may result from a clear failure of one's "old" ideology) motivates individuals to develop a very positive or extremely positive national attitude (see Blank, 1997;Bloom, 1990;Csepeli & Örkény, 1993;Mummendey, Klink, Mielke, Wenzel, & Blanz, 1999;Smith, 1991;Tajfel & Turner, 1986;Weinreich, 1991).…”
Section: Hypotheses Explaining Nationalismmentioning
confidence: 99%